2009
DOI: 10.1242/jeb.023911
|View full text |Cite
|
Sign up to set email alerts
|

Developmental adjustments of house sparrow (Passer domesticus)nestlings to diet composition

Abstract: SUMMARYHouse sparrow nestlings are fed primarily on insects during the first 3 days of their life, and seeds become gradually more important afterwards. We tested whether developmental changes in size and functional capacity of the digestive tract in young house sparrows are genetically hard-wired and independent of diet, or can be modified by food type. Under laboratory conditions, we hand-fed young house sparrows with either a starch-free insect-like diet, based mainly on protein and fat, or a starchcontaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(99 citation statements)
references
References 45 publications
6
93
0
Order By: Relevance
“…While some of the habitat characteristics (like pH or oxygen levels) could have important effects on the bacterial communities, the reduction in the diversity and availability of metabolizable substrates along the gut is probably the reason for the decreasing diversity of bacterial genera and species along the gut of the House Sparrow (Figures 3(a) and 3(b)) [41,55,59]. Previous studies of the physiology of this species showed that the activity of intestinal enzymes decreased along the gut as a response of a reduction of nutrients [9].…”
Section: Bacterial Composition Along the House Sparrow's Gutmentioning
confidence: 90%
See 2 more Smart Citations
“…While some of the habitat characteristics (like pH or oxygen levels) could have important effects on the bacterial communities, the reduction in the diversity and availability of metabolizable substrates along the gut is probably the reason for the decreasing diversity of bacterial genera and species along the gut of the House Sparrow (Figures 3(a) and 3(b)) [41,55,59]. Previous studies of the physiology of this species showed that the activity of intestinal enzymes decreased along the gut as a response of a reduction of nutrients [9].…”
Section: Bacterial Composition Along the House Sparrow's Gutmentioning
confidence: 90%
“…The dominance of Firmicutes and Proteobacteria in the intestinal bacterial communities has been reported for other birds like Zebra Finches [8], as well as wild and captive parrots [73]. Because Proteobacteria is a group with a high functional diversity [29], the dominance of Proteobacteria in the House Sparrow gut could be related to its omnivorous diet that includes seeds, insects, fruits, and a large diversity of human food scraps including meat [9,11,49]. This diverse diet provides bacterial communities with a high diversity of substrates.…”
Section: Bacterial Composition Along the House Sparrow's Gutmentioning
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, recently, Brzek (2009) documented that specifi c maltase activity can be modulated during development in nestlings of house sparrows (Passer domesticus), but not in adult birds (Cavides-Vidal et al, 2000), suggesting that the magnitude of modulation in enzyme activities can be largely underestimated when using adult animals as experimental subjects. Unfortunately, few studies on the physiological diversity of birds have partitioned phenotypic variation (Biviano et al, 1993;Brzek et al, 2009), and hence it remains unknown how much of intra-specifi c variability in enzyme activities has a genetic basis or is attributable to phenotypic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Meynard et al (1999), found a higher activity of maltase in the hervibore passerine Phytotoma rara, an expected result given the high carbohydrate diet of this animal. On the other hand, it has been documented that the activity of brush border enzymes can be strongly affected by the levels of specifi c substrates in both the fi eld and the laboratory (Martinez del Sabat et al, 1999;Caviedes-Vidal et al, 1994;Karasov et al, 1997;Sabat et al, 1998;Caviedes-Vidal et al, 2000;Brzek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%